RT ADMINISTRATIVE GOVERNANCE ASSISTANCE. 02/027 TGA HOUSING BLOCK GM IN THE ERA OF DIGITALIZATION: PENDAMPINGAN TATA KELOLA ADMINISTRASI RT. 02/027 PERUMAHAN TGA BLOK GM DI ERA DIGITALISASI - Hafidz Hanafiah; Budi Susanto (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Rukun Tetangga is in coordination with the Rukun Warga and part of the village or village. The technical implementation of the RT is in charge of bridging agencies or organizations outside other external RTs that have the legality of the village or village. Related to administrative governance RT often faces the problem of archives that can only be accessed on one technological tool such as a laptop or computer, this makes the management and governance process long, especially when the management is outside the residential area of the complex. Along with the development of the digital era, administrative governance and archives of Rukun Tetangga can use Google Drive and QR-Code. In the implementation of PKM this time, an analysis was carried out first on housing problems, especially complex houses, then socialization, then assistance and implementation in the RT area. 002 Housing Taman Graha Asri Block Graha Minimalist in Serang City. As for the results that can be a benefit for the RT management. 002 is can be done anywhere, anytime, without the administrator having to meet often because of their respective busy lives. This makes it easier for the management to manage the administration of the RT.002 residents